Certolizumab pegol plus methotrexate 5-year results from the rheumatoid arthritis prevention of structural damage (RAPID) 2 randomized controlled trial and long-term extension in rheumatoid arthritis patients - Smolen, Josef S; van Vollenhoven, Ronald; Kavanaugh, Arthur; Strand, Vibeke; Vencovsky, Jiri; Schiff, Michael; Landewé, Robert; Haraoui, Boulos; Arendt, Catherine; Mountian, Irina; Carter, David; van der Heijde, Désirée (Arthritis research & therapy, 2015)
INTRODUCTION: As patients with rheumatoid arthritis (RA) receive treatment with anti-tumour necrosis factors over several years, it is important to evaluate their long-term safety and efficacy. The objective of this study was to examine the safety and benefits of certolizumab pegol (CZP)+methotrexate (MTX) treatment for almost 5 years in patients with RA. METHODS: Patients who completed the 24-week Rheumatoid Arthritis Prevention of Structural Damage (RAPID) 2 randomized controlled trial (RCT; NCT00160602), or who were American College of Rheumatology (ACR) 20 non-responders at Week 16, entered the open-label extension (OLE; NCT00160641). After ≥6 months treatment with CZP 400 mg every two weeks (Q2W), dose was reduced to 200 mg Q2W, the approved maintenance dose. Safety data are presented from all patients who received ≥1 dose CZP (Safety population, n=612). Efficacy data are presented to Week 232 for the intent-to-treat (ITT, n=492) and Week 24 CZP RCT Completer (n=342) populations, and through 192 weeks of dose-reduction for the Dose-reduction population (patients whose CZP dose was reduced to 200 mg, n=369). Radiographic progression (modified total Sharp score change from RCT baseline >0.5) to Week 128 is reported for the Week 24 CZP Completers. RESULTS: In the RCT, 619 patients were randomized to CZP+MTX (n=492) or placebo+MTX (n=127). Overall, 567 patients (91.6%) entered the OLE: 447 CZP and 120 placebo patients. Of all randomized patients, 358 (57.8%) were ongoing at Week 232. Annual drop-out rates during the first four years ranged from 8.4-15.0%. Event rates per 100 patient-years were 163.0 for adverse events (AEs) and 15.7 for serious AEs. Nineteen patients (3.1%) had fatal AEs (incidence rate=0.8). Clinical improvements in the RCT were maintained to Week 232 in the CZP Completers: mean Disease Activity Score 28 (Erythrocyte Sedimentation Rate) change from baseline was -3.4 and ACR20/50/70 responses 68.4%/47.1%/25.1% (non-responder imputation). Similar improvements observed in the ITT were maintained following dose-reduction. 73.2% of CZP Completers had no radiographic progression at Week 128. CONCLUSIONS: In patients with active RA despite MTX therapy, CZP was well tolerated, with no new safety signals identified. CZP provided sustained improvements in clinical outcomes for almost 5 years. TRIAL REGISTRATION: ClinicalTrials.gov, NCT00160602 and NCT00160641 . Registered 8 September 2005.
Keywords: Drug Administration Schedule; Adult; Kaplan-Meier Estimate; Arthritis, Rheumatoid; Certolizumab Pegol; lidé středního věku; Antirheumatic Agents; kombinovaná farmakoterapie; výsledek terapie; Drug Therapy, Combination; certolizumab pegol; rozvrh dávkování léků; Dose-Response Relationship, Drug; ženské pohlaví; Kaplanův-Meierův odhad; revmatoidní artritida; lidé; vztah mezi dávkou a účinkem léčiva; antirevmatika; mužské pohlaví; senioři; časové faktory; dospělí; methotrexát; Treatment Outcome; Aged; Humans; infekce; Infections; Methotrexate; Female; Middle Aged; Male; Time Factors